Red light running by cyclists. Which factors influence the red light negating cyclist? - Meel, Evelien Martine van der (My University, 2013)
Jährlich werden in den Niederlanden mehr als 20.000 Menschen bei Unfällen verletzt, fast die Hälfte der erfassten Unfälle treten an Knotenpunkten auf. Um die Zahl der Konflikte an Knotenpunkten zu minimieren, sind zahlreiche Kreuzungen mit Lichtsignalanlagen ausgestattet. Diese sind allerdings nur nutzenbringend, wenn sie auch beachtet werden. Die meisten Ampelanlagen sind auf den motorisierten Verkehr zugeschnitten, da dieser die größten Raum und die längste Zeit benötigt, den Kreuzungsbereich zu räumen. Fahrradfahrer haben vergleichsweise lange Wartezeiten, obwohl sie in geringerer Zeit und in größerer Anzahl den Kreuzungsbereich passieren können. Möglicherweise sind Fahrradfahrer deshalb eher geneigt, rote Ampeln zu ignorieren und Kreuzungen dann zu passieren, wenn es ihnen sicher erscheint. Das Überqueren bei Rot wird "red light running" genannt. Der Bericht hat das Ziel, die Prozentzahl der Radfahrer in den Niederlanden zu ermitteln, die Ampeln bei Rot überqueren sowie die Einflussfaktoren darauf und Konsequenzen für die Verkehrssicherheit zu untersuchen. Die Literaturrecherche ergab verschiedene Einflussfaktoren. Ein Großteil der Fahrradfahrer, die Ampeln bei Rot überqueren, ist männlich, im jungen Erwachsenenalter und erfahrener Fahrradfahrer. Weitere Einflussfaktoren sind schlechtes Wetter, lange Wartezeiten, geringer Verkehrsfluss, kurze zu überquerende Distanzen, "Gruppenzwang" (wenn auch andere Personen die Straße überqueren, folgt man schneller) sowie eine geringe Anzahl von LKWs und Bussen.

Over 20,000 people get injured in a crash in the Netherlands each year, nearly the half of these registered crashes take place at intersections. To minimize the number of conflicts many intersections are controlled by traffic signals, but these will only have effect when the signals are obeyed. In nearly all traffic signal control systems the motorised streams are prioritised, because of the space and time needed for cars to cross the intersection. Cyclists, who can cross in high numbers in a short time, have longer waiting times compared to motorized streams. As a result cyclists are possibly more likely to ignore the traffic lights and cross when seems safe to them. When they cross during the phase where the light is turned red, this is called red light running. The purpose of the report is to give insight in the percentage of the red light running by cyclists in the Netherlands, the influence factors and the consequences for traffic safety. Through literature review an inventory of the different factors that influence red light running is made. The characteristics found that increased the percentage of red light running were: Male cyclists, young adults, experienced cyclists, bad weather, long waiting times, reduced credibility/low conflicting traffic flow, short crossing distance, herding (when there are other people violating the red light they are more likely to also violate the red light) and a low percentage of trucks and busses. With the help of video observations on 5 different intersections, factors found in literature were analysed. The overall red light running was 27.4%. Factors that were found influencing red light running are: - Gender: Men violated the red light 1.32 times more than women. - Age: Young cyclist have a higher percentage of red light running, 1.63 times higher than adults and 1.78 time higher than elderly cyclists. - Crossing distance: A longer crossing distance decreases the red light running - Flow of the motorized streams: more traffic on the conflicting motorized streams lead to less red light running.
Keywords: Individualverkehr; Fahrradverkehr; Straßenverkehr; Verkehrsverhalten; Lichtsignalanlage; Verkehrsknoten; Verkehrssicherheit; Straßenverkehrsregelung; Schaltung; Verkehrsunfall; Verkehrsbeschleunigung; Vorrangschaltung; Mobilitätsforschung; Studie; Verkehrssteuerung